1997
DOI: 10.1029/96jd03880
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional reflectance of selected BOREAS sites from multiangle airborne data

Abstract: Abstract. Hyperspectral, multiangle reflected radiances were obtained using the airborne advanced solid-state array spectroradiometer (ASAS) over Boreal Ecosystem-Atmosphere Study (BOREAS) sites in Canada during four field campaigns in 1994. Atmospherically corrected bidirectional reflectance factors and estimates of spectral hemispherical reflectance for three canopies in the BOREAS southern study area (old aspen, old black spruce, and old jack pine) are presented. The multiangle spectral reflectance factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…This method yielded a strong agreement (r 2 = 0.8) with fluxes determined by eddy covariance from five different boreal ecosystems (Rahman et al, 2001). the confirmation that BRDF signatures vary predictably with the dominant land-cover types, offering a novel means of mapping vegetation for the boreal forest region (see Russell et al, 1997;Sandmeier & Deering, 1999). Furthermore, the specular component of the BRDF helps isolate inundated areas such as fens (e.g., Vanderbilt et al, 2002), which are important regional sources of methane.…”
Section: Improved Land-cover Classificationmentioning
confidence: 62%
See 3 more Smart Citations
“…This method yielded a strong agreement (r 2 = 0.8) with fluxes determined by eddy covariance from five different boreal ecosystems (Rahman et al, 2001). the confirmation that BRDF signatures vary predictably with the dominant land-cover types, offering a novel means of mapping vegetation for the boreal forest region (see Russell et al, 1997;Sandmeier & Deering, 1999). Furthermore, the specular component of the BRDF helps isolate inundated areas such as fens (e.g., Vanderbilt et al, 2002), which are important regional sources of methane.…”
Section: Improved Land-cover Classificationmentioning
confidence: 62%
“…Moreover, BOREAS has been successful in clarifying the contribution of multi-scale and directional radiative effects necessary to improve radiation schemes in climate models Li et al, 1997;Russell et al, 1997;Sandmeier & Deering, 1999). Scaling strategies consisting of comparing remotely sensed radiances from tower scale to patch scale and finally to regional scale (including water bodies) are leading to a new generation of radiative transfer models which account for grouping effects across scales.…”
Section: Links Between Surface Properties Weather and Climatementioning
confidence: 99%
See 2 more Smart Citations
“…In line with this assumption, earlier studies have treated satel-61 lite BRDF/albedo retrievals as being observed over a homogeneous landscape; thus allowing di-62 rect -point-to-pixel‖ comparisons ( sub-grid scale spatial heterogeneity, and other underlying sources of variation that introduce 69 measurement uncertainties within the ground resolution element (GRE) of satellite retrievals; the 70 BRDF (and thus albedo) of certain ecosystems can only be correctly sampled with airborne mul-71 tiangle measurements (Walthall et al 2000). Among key biomes affected by these sources of er-72 ror are mixed-forest canopies (Johnson 1994;Russell et al 1997b), tropical savannas (Hill et al 73 2008; Georgiev et al 2009), shrublands (Chopping et al 2004), as well as snow-covered envi-74 ronments (Lyapustin et al 2009). Furthermore, recent studies contend that subpixel vegetation 75 structure is only detectable when obtaining measurements near the principal plane; i.e., where 76 BRDF effects are most pronounced (Chen et al 2005).…”
Section: Introduction 47mentioning
confidence: 99%